2009
DOI: 10.3928/00220124-20090623-05
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Clinical Adjunct Role to Benefit Students

Abstract: This article describes solutions to one of the challenges that nursing programs throughout the nation face--the employment of clinically expert nurse practitioners and clinical nurse specialists as clinical adjunct faculty who lack the educational foundation to teach students. Some of the difficulties experienced by clinical adjunct faculty, university administrators, and full-time faculty are presented. Solutions described include a clinical adjunct workshop, collaboration between hospitals and universities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…For example, part-time faculty members allow universities and departments flexibility in responding to variable student enrollment. While some suggested that part-time faculty are less expensive than full-time faculty (Baldwin & Wawrzynski, 2011), others highlighted rising pay rates for some part-time faculty, such as nursing adjuncts (West et al, 2009). In addition to external market forces for full-time faculty, there are increasing internal academic pressures that have to be balanced with teaching responsibilities.…”
Section: Benefits Of Part-time Facultymentioning
confidence: 98%
“…For example, part-time faculty members allow universities and departments flexibility in responding to variable student enrollment. While some suggested that part-time faculty are less expensive than full-time faculty (Baldwin & Wawrzynski, 2011), others highlighted rising pay rates for some part-time faculty, such as nursing adjuncts (West et al, 2009). In addition to external market forces for full-time faculty, there are increasing internal academic pressures that have to be balanced with teaching responsibilities.…”
Section: Benefits Of Part-time Facultymentioning
confidence: 98%
“…Methods for promoting confidence and assisting positive enrichment include peer groups (Duphily, 2011;West et al, 2009), on-line discussion and connection (Duphily, 2011;Peters & Boylston, 2006;West et al, 2009), development of a reference manual (Pierangeli, 2006), and clinical teaching in hospital where employed (Parslow, 2008). Other formal mentoring designs for clinical nursing have incorporated Blackboard (West et al, 2009), an on-line semester mentoring course encompassing components of curriculum, simulation, and evaluation methods (Bell-Scriber & Morton, 2009), and formal faculty practicum workshops to the clinical unit and orientation programs (Hutchinson, Tate, Torbeck, & Smith, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meaningful and fulfilling work is important to prevent burnout 20,21 . It follows that in order for the part‐time teachers to excel in their roles as educators, and for their experience to be personally and professionally rewarding, there has to be a commitment from both the teacher and the department, school or college that every effort will be made to achieve success 22,23 . The part‐time teacher must understand that this will entail work beyond just the hours in the classroom.…”
Section: Strategies To Maximise the Potential Of Part‐time Teachersmentioning
confidence: 99%